Genealogy and Reform of Islamic Family Law: Study of Islamic Marriage Law Products in Malaysia - Siti Aminah; Arif Sugitanata (Journal of Islamic Law)
As an Islamic country, Islamic family law reform in Malaysia is experiencing various dynamics. This article aims to examine the genealogy, reform, and products of Islamic family law in the field of marriage (munakahat) in Malaysia. The authors find that Malaysia’s Islamic law reform is divided into three periods using literature research. In the Malay period, Islamic values were generally embedded in the law in Malaysia. During the British colonial period, English law had dominated and was used as common law, which was absorbed in various legislation and jurisprudence in Malaysia. It was only after independence that efforts to reform and codify Islamic family law began, marked by the stipulation of the jurisdiction of the federal territorial government and the territorial government into thirteen states. The codification of family law began with establishing a committee to amend Islamic law and be guided by other Islamic countries. The authors find four areas of marriage that have been reformed in Malaysia, namely the age limit for marriage, marriage registration, polygamy, and divorce. Among the four areas of marriage law, the authors find slight differences in regulations on the technical and material grounds in each state in Malaysia.